Development of VOLT BANK: Operating System and Charge Management for Battery-Equipped Medical Equipment. Issue 2 (April 2015) - Yoshioka, Jun; Murakami, Masayasu; Sadahiro, Mitsuaki; Fujita, Masaki
Abstract : This study describes a battery-charging rack (VOLT BANK) that was developed and implemented in our institution. A charge-control box was created with a 100-V cutoff function, and a special rack was incorporated. In the 100-V cutoff function, when the batteries are fully charged, the equipment automatically turns off the power supply of 100 V, in the order that they finish charging. A maximum of 36 medical devices can be simultaneously charged and stored. This rack was thought to enable construction of a safe, smoothly operating system for battery-equipped medical equipment and efficient battery-charge management that prevents overcharge and electrical discharge.